Acupuncture Care In Patients With Adhesive Capsulitis At Griya Sehat Sapu Bersih, South Tangerang - Purnama, Rully Indra; Kurniawan, Leny; Wardoyo, Puspo (Jurnal Indonesia Sosial Sains, 2025)
This study aims to evaluate the benefits of Acupuncture Care in patients with Adhesive Capsulitis at Griya Sehat Sapu Bersih, South Tangerang. The method used was a qualitative approach with a case study, involving one 58-year-old participant who experienced right shoulder pain for six months. Data were collected through observation, interviews, and physical examinations, and analyzed to determine the diagnosis of acupuncture. The results showed that after six sessions of acupuncture therapy, there was a significant decrease in the pain scale from 7 to 2, as well as an increase in shoulder range of motion. These findings indicate that acupuncture is effective in relieving pain and improving mobility in patients with Adhesive Capsulitis. This research is expected to be a reference for the further development of acupuncture therapy in the treatment of similar conditions.